Efisiensi Biaya dalam Implementasi ABM: Analisis Tinjauan Literatur Sistematis - Pramana Dwi Syahputra; Muhammad Rafli Gunawan Saputra; Rakha Maulana; Salsabilla Nadya Chanyesa; Yusnaini (Publikasi Inspirasi Indonesia, 2025)
This study aims to systematically identify and analyze the factors influencing the effectiveness of Activity-Based Management in improving cost efficiency in companies. Using the systematic literature review method, 27 scientific articles published between 2019 and 2025 were selected and analyzed to extract relevant information regarding internal and external factors that support or hinder the implementation of this cost management approach. The findings reveal a total of 12 influencing factors, with business competition being the most dominant factor, followed by data availability and consumer demands. These results indicate that the success of Activity-Based Management in enhancing cost efficiency is not only dependent on internal readiness, such as employee competence and accounting information systems, but also strongly affected by external pressures such as market competition and regulatory dynamics. This study contributes to a more comprehensive understanding of how various factors interact in shaping the effectiveness of Activity-Based Management and provides useful insights for managers seeking to optimize operational activities and reduce non-value-added costs through informed, data-based decision-making.